THE INCREASE OF EFFICIENCY OF ASSOCIATION OF THE DATA FOR STABILITY AERONAVIGATION SYSRWM IN THE EVENT CORRELATED OBSERVATION GAUSSIAN DENSITY - Слюняєв, О. (Science-based technologies, 2011)
The technique of increase of efficiency of association of the data in case of Gaussian density for the purpose of optimization of statistically distributed revealing is considered and work of the concentrated processor which provides faster decision-making uniting decisions of separate receivers.